Relationship between serum carotenoids and osteoarthritis or degenerative arthritis: A cross-sectional study using the National Health and Nutrition Examination Survey - Bowen Zhu; Guochun Li; Kaiwen Wu; Qian Luo; Xie Wu (Nutrition Journal)
Abstract Background Carotenoids possess essential antioxidant and anti-inflammatory properties; however, the relationships between carotenoids and osteoarthritis or degenerative arthritis (OA) remain inadequately understood. This study aimed to investigate the correlation between diverse serum carotenoid concentrations and OA in a large American cohort and to examine the influence of various factors on the association between carotenoids and OA. Methods Data from the 2001–2006 and 2017–2018 National Health and Nutrition Examination Surveys were utilized. In our analysis, we utilized a directed acyclic graph to identify potential confounding variables. The associations between serum carotenoids (including total carotenoid, trans-lycopene, β-cryptoxanthin, lutein/zeaxanthin, α-carotene, and β-carotene) and OA were comprehensively evaluated via a weighted generalized linear model (GLM) and restricted cubic spline models. Threshold effect analyses were used to identify potential cutoff points, subgroup analyses were used to explore heterogeneity, interaction analyses were used to examine potential modifiers, and sensitivity analyses were used to validate the robustness of the findings. Results The weighted GLM results revealed that, overall, the concentrations of various serum carotenoids did not exhibit a significant linear correlation with the probability of OA. Dose‒response curves and threshold effect analysis revealed a significant nonlinear relationship (P for overall = 0.027; P for nonlinearity = 0.019; P for likelihood ratio = 0.0128) between trans-lycopene (threshold effect) and OA, with an inflection point at 19.49 µg/dl. Further subgroup weighted linear regression analysis indicated that when the serum trans-lycopene concentration exceeded 19.49 µg/dl, there was a significant association [odds ratio (OR) = 0.89 (0.80–0.99); P = 0.027] between the per standard deviation trans-lycopene increase and a lower probability of OA after adjusting for other variables. Moreover, individuals with elevated trans-lycopene [0.70 (0.52–0.94); P = 0.018] in the fifth quintile had notably reduced odds of OA compared with those in the first quintile. When the trans-lycopene level is less than 19.49 µg/dl, no correlation exists between the two variables. Linear subgroup and interaction analyses revealed that when the concentration of carotenoids exceeded 19.49 µg/dl, various categorical factors did not significantly influence the relationship between trans-lycopene and OA overall. However, pairwise comparisons revealed that lower serum trans-lycopene concentrations are more closely associated with a greater probability of OA in elderly individuals [OR (95% CI) = 0.270 (0.112–0.654); P = 0.005; P for trend = 0.003] than in younger individuals [0.973 (0.385–2.463); P = 0.954; P for trend = 0.61] (P for interaction = 0.007). Conclusions In the American population, trans-lycopene rather than other types of carotenoids may exhibit a significantly negative correlation with OA, displaying a nonlinear pattern with a threshold point of approximately 19.49 µg/dl. This relationship may become more pronounced with increasing age.